An ecological perspective on the flow of compassion among Iranian learners of English as a foreign language - Wang, Gang; Soleimanzadeh , Soheila; Elahi Shirvan, Majid (Studies in Second Language Learning and Teaching, 2023)
As a social-interactional positive behavior, the flow of compassion (i.e., self-compassion, compassion for others, and compassion from others), which refers to sensitivity to suffering in self and others with a commitment to try to alleviate and prevent it, has yet to be investigated in a highly social-interactional context such as foreign language learning classrooms. Thus, the present study adopted an ecological perspective within Bronfenbrenner’s (1979, 1993) analytic nested ecosystems model to explore how the flow of compassion is rooted in such a context. Sixteen Iranian English as a foreign language learners took part in the current study, and data were collected through semi-structured interviews. Employing the framework of the nested ecosystems model, we identified both influential individual and environmental factors underlying the flow of compassion among the participants. The flow of compassion proved to be influenced differently at different ecosystemic levels by individual and environmental factors. At the individual level, negative and positive emotions, fears, non-judgmental attitudes, intimacy, well-being, improvement, motivation, and action were found as influential factors in emerging the flow of compassion. At the contextual level, the identified influential factors included past experiences outside of the classroom, extracurricular activities, institution policy and criteria, cultural and social values, as well as the use of technology and the internet. Limitations and implications of the present study are also discussed.